Increase of circulating IGFBP-4 following genotoxic stress and its implication for senescence - Nicola Alessio; Tiziana Squillaro; Giovanni Di Bernardo; Giovanni Galano; Roberto De Rosa; Mariarosa AB Melone; Gianfranco Peluso; Umberto Galderisi (eLife)
Senescent cells secrete several molecules, collectively named senescence-associated secretory phenotype (SASP). In the SASP of cells that became senescent following several in vitro chemical and physical stress, we identified the IGFBP-4 protein that can be considered a general stress mediator. This factor appeared to play a key role in senescence-paracrine signaling. We provided evidences showing that genotoxic injury, such as low dose irradiation, may promote an IGFBP-4 release in bloodstream both in mice irradiated with 100 mGy X-ray and in human subjects that received Computer Tomography. Increased level of circulating IGFBP-4 may be responsible of pro-aging effect. We found a significant increase of senescent cells in the lungs, heart, and kidneys of mice that were intraperitoneally injected with IGFBP-4 twice a week for two months. We then analyzed how genotoxic stressors may promote the release of IGFBP-4 and the molecular pathways associated with the induction of senescence by this protein.